Hepatoprotective effect of Phyllanthus niruri ethanolic extract on alcohol and high cholesterol diet-induced liver cell damage in rats - Tan, Lai Ting (2015)
Phyllanthus niruri, locally known as “Dukung Anak” is well-known for its therapeutic effect against hepatitis, urolithiasis, dysentery, influenza, jaundice and bacterial infection. Alcoholic liver disease (ALD) is a liver disease in human caused by alcohol consumption. It is a spectrum of disease which started from hepatic steatosis to steatohepatitis and finally hepatic cirrhosis in chronic cases. In this study, the hepatoprotective effect of Phyllanthus niruri ethanolic extract was evaluated on alcohol and high cholesterol diet-induced liver cell damage in rats. A total of 20 rats were randomly divided into 5 groups comprised of group A (control), group B (alcohol and high cholesterol diet), groups C, D and E (given alcohol and high cholesterol diet, and supplemented with Phyllanthus niruri ethanolic extract at 75 mg/kg, 150 mg/kg, and 250 mg/kg respectively. The evaluation was carried out through analysis of liver parameters, lipid parameters and histopathological examination of liver at the end of experiment. Result showed that the relative liver weight of group C (3.36±0.07), D (3.35±0.11) and E (3.15±0.19) were significantly (p< 0.05) lower than group B (3.84±0.22). The serum low density lipoprotein (LDL) level was significantly (p<0.05) higher in group B (0.88±0.14 mmol/L) compared to Group A (0.49±0.05 mmol/L), D (0.62±0.06 mmol/L) and E (0.62±0.11mmol/L). However, there were no significant differences on liver parameters in all groups. The histopathological evaluation of the liver revealed that group B was having the highest steatosis score and both group A and E were having nearly similar steatosis score. In conclusion, Phyllanthus niruri ethanolic extract has hepatoprotective effect against alcohol and high cholesterol diet-induced liver injury in rats.